Visible Light Promoted Catalyst Free, the Sustainable Synthesis of Dihydropyrano [2,3-C] Pyrazoles and Docking Studies with COVID-19 Mpro (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
A highly efficient, simple, cost effective, and eco-friendly protocol has been developed for synthesis of dihydropyrano[2,3-c]pyrazoles via one-pot, three-component condensation of 3-methyl-1-phenyl-2-pyrazoline-5-one, malononitrile, substituted aromatic aldehydes under visible light irradiation in catalyst-free condition at room temperature. The main advantage of this methodology is good to excellent yield, simple work-up procedure, mild and clean reaction conditions, no chromatographic separation, environmentally benign reaction conditions, and catalyst free, the application of clean visible-light as a source of energy. The synthesized compounds are screened in silico with 6LU7, which is a COVID-19 Mpro. Compound 4i and nitro group compounds 4d, 4e, 4f are showing strong correlation at the active center of 6LU7. So, it is predicted that these compounds may be useful for COVID-19 patients.